2022
DOI: 10.1200/jco.21.01774
|View full text |Cite
|
Sign up to set email alerts
|

Indications and Parameters Around Postoperative Radiation Therapy for Lung Cancer

Abstract: Patients with locally advanced resected non–small-cell lung cancer present a high risk of relapse. Although adjuvant platinum–based chemotherapy has become the standard of care, the role of postoperative radiation therapy (PORT) has been controversial for years. In patients with incomplete resection, PORT should be proposed, on the basis of a strong consensus, despite the absence of randomized evidence. In patients with completely resected (R0) non–small-cell lung cancer, a meta-analysis showed poorer outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 73 publications
(178 reference statements)
0
10
0
Order By: Relevance
“…Current data shows that neoadjuvant chemotherapy improved the OS by around 5% in OS and time to recurrence in patients with resectable NSCLC ( 3 ). The addition of radiation to neoadjuvant chemotherapy did not seem to further improve the survival benefit ( 4 ). Radiation gives help to control locoregional disease, but the PFS extension fails to translate into a long-term survival benefit ( 5 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Current data shows that neoadjuvant chemotherapy improved the OS by around 5% in OS and time to recurrence in patients with resectable NSCLC ( 3 ). The addition of radiation to neoadjuvant chemotherapy did not seem to further improve the survival benefit ( 4 ). Radiation gives help to control locoregional disease, but the PFS extension fails to translate into a long-term survival benefit ( 5 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative radiation therapy (PORT) for non-small cell lung cancer (NSCLC) is controversial. 1 Many retrospective and large public database studies have suggested that PORT confers survival benefits for patients with pathologic N2 NSCLC 2 , 3 ; however, 2 recent randomized controlled trials showed that PORT does not improve progression-free survival (PFS) or overall survival (OS) in these patients. 4 , 5 Cardiopulmonary toxic effects may diminish the benefit of PORT.…”
Section: Introductionmentioning
confidence: 99%
“…Radiotherapy can have detrimental effects on immunonutritional status in two ways: (1) radiation damage to lymphocytes and hematopoietic organs, and (2) radiationinduced fatigue, poor oral intake, and anorexia. The aim of our study was to determine the value of PNI in the prognosis of NSCLC patients with PORT.…”
Section: Introductionmentioning
confidence: 99%